(untitled) (Per Musi, 2022)
Emotional experiences, including anxiety, are made up of subjective physiological and behavioral components (Valentine 2002). In controllable amounts, anxiety can incite the individual to respond positively to a stimulus, however, it only does so up to the point where the organism reaches a maximum level of tolerance; beyond this point, the ability to handle and adapt can decrease, which, in a context of musical performance, can be harmful. Based on the review of Performance Anxiety concepts developed by authors in the area (Valentine 2002; Kenny 2011; Papageorgi 2007), we point out the need for a specific approach regarding management strategies, as well as guidance for their proper use based on from a Sport Psychology perspective.